PENGEMBANGAN E-EVALUASI PEMBELAJARAN BERBANTUAN WORDWALL PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA: Penelitian Research and Development - Rahma Alfiani Islamia; Yuli Mulyawati; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study uses the Research and Development (R&D) approach with the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were students of grade IV of Cipatat State Elementary School, Bogor Regency, consisting of 20 students, the study was conducted in the even semester of the 2024/2025 school year. The purpose of this study was to develop and determine how to test the feasibility of the Development of E-Evaluation Assisted by Wordwall in the learning process in the classroom. The results of the study showed that the Development of E-Evaluation Assisted by Wordwall has a feasibility criterion of "Very Feasible" for use. This can be seen from the results of the validity test from the experts, namely media experts with a percentage of 95%, material experts 97.5%, and language experts 97.5% with the category of "Very Feasible" criteria in the range of 80% -100%. In addition, the students' response to the Development of E-Evaluation Assisted by Wordwall obtained a percentage result of 98.3% with the category of "Very Eligible" for use. Then the results of the Pretest and Posttest obtained an N-Gain result of 0.61 with the criteria of "Moderate" between the range of 0.30 ≤ G < 0.70. Thus, it can be concluded that the Development of E-Evaluation Assisted by Wordwall is very feasible for use.